2018
DOI: 10.1097/ccm.0000000000003441
|View full text |Cite
|
Sign up to set email alerts
|

Combining National Early Warning Score With Soluble Urokinase Plasminogen Activator Receptor (suPAR) Improves Risk Prediction in Acute Medical Patients: A Registry-Based Cohort Study*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 26 publications
5
71
1
14
Order By: Relevance
“…From a clinical point of view, this marker has been linked to quite a range of complications and adverse prognosis in manifold disease settings [4,8,31], and even in seemingly healthy volunteers [32,33]. The ability of suPAR to help in risk stratification is particularly interesting in the emergency room [34,35] or the ICU setting [18,36], where acutely ill patients require an early risk assessment to tailor therapeutic interventions and allocate appropriate ICU resources. However, despite its practical utility for prognostication in the ICU setting, suPAR appears to be quite non-specific as to the cause of disease, to the presence of sepsis and to the nature of concomitant organ failure(s) [30].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, this marker has been linked to quite a range of complications and adverse prognosis in manifold disease settings [4,8,31], and even in seemingly healthy volunteers [32,33]. The ability of suPAR to help in risk stratification is particularly interesting in the emergency room [34,35] or the ICU setting [18,36], where acutely ill patients require an early risk assessment to tailor therapeutic interventions and allocate appropriate ICU resources. However, despite its practical utility for prognostication in the ICU setting, suPAR appears to be quite non-specific as to the cause of disease, to the presence of sepsis and to the nature of concomitant organ failure(s) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the predictive ability of the NEWS increases on combining several lab-oratory results with the NEWS. 9,[20][21][22] This combination method should also be validated in older patients to improve predictive ability in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…The available test allows a fast prognosis for patients, as the results can quickly be obtained on-site in the emergency room or other in-hospital settings, avoiding the need for samples to be passed through the clinical laboratory, or can even be obtained prior to hospitalization (time to result 20 min). Based on the aforementioned evidence, the suPAR could serve as a quick triage test and independent marker of clinical severity, 30-day readmission, complications, and mortality in this pandemic [10,19,35,36]. We believe that the results of ongoing trials in Germany, the UK, Denmark, Greece, and the USA will be important for clinicians worldwide.…”
Section: Soluble Urokinase Plasminogen Activator Receptormentioning
confidence: 98%
“…In a study of 42,452 acutely presenting patients, suPAR had the highest area under the curve of all investigated individual predictors, including C-reactive protein (CRP), while there was no significant difference in the predictive value between age groups [9]. In another study, including 17,312 acutely admitted medical patients, the addition of suPAR to National Early Warning Score significantly improved risk prediction of both low-and highrisk acute medical patients [10]. Interestingly, patients with low National Early Warning Score, but elevated suPAR had mortality risks comparable to that of patients with higher National Early Warning Score.…”
Section: Soluble Urokinase Plasminogen Activator Receptormentioning
confidence: 99%